2016
DOI: 10.1016/j.amjmed.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognosis of Hyperkalemia in Patients with Acute Myocardial Infarction

Abstract: Background Hyperkalemia is common and potentially dangerous in hospitalized patients; its contemporary prevalence and prognostic importance following acute myocardial infarction are not well described. Methods In 38,689 consecutive acute myocardial infarction patients from the Cerner Health Facts database, we evaluated the association between maximum in-hospital potassium levels (max K) and in-hospital mortality. Patients were stratified by dialysis status, and grouped by max K as follows: <5 mEq/L, 5–<5.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…Furthermore, An et al 31 showed a graded decrease in risk of death among patients with extreme levels of hyperkalemia (.6.5 meq/L) as CKD stage increased (OR for death with stage 2, 3, 4, and 5 CKD, 0.52; 95% CI, 0.35 to 0.78, 0.31; 95% CI, 0.21 to 0.46, 0.13; 95% CI, 0.06 to 0.26, and 0.17; 95% CI, 0.11 to 0.27). Similar results were observed among dialysis versus non-CKD patients with hyperkalemia and AMI in the studies performed by Goyal et al 37 and Grodzinsky et al 38 One prospective observational analysis of sustained hyperkalemia and outcomes in patients with creatinine clearance ,50 ml/min demonstrated that hyperkalemia in the ranges of 5.0-6.0 meq/L (using an average of six measurements per patient) appeared to be well tolerated. 47 Adaptive increases in circulating catecholamines, aldosterone, and augmentation of renal and gastrointestinal (GI) potassium elimination are thought to blunt hyperkalemia development in CKD and could partially explain this apparent disconnect in mortality relative to non-CKD patients.…”
Section: Hyperkalemia With Ckdsupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, An et al 31 showed a graded decrease in risk of death among patients with extreme levels of hyperkalemia (.6.5 meq/L) as CKD stage increased (OR for death with stage 2, 3, 4, and 5 CKD, 0.52; 95% CI, 0.35 to 0.78, 0.31; 95% CI, 0.21 to 0.46, 0.13; 95% CI, 0.06 to 0.26, and 0.17; 95% CI, 0.11 to 0.27). Similar results were observed among dialysis versus non-CKD patients with hyperkalemia and AMI in the studies performed by Goyal et al 37 and Grodzinsky et al 38 One prospective observational analysis of sustained hyperkalemia and outcomes in patients with creatinine clearance ,50 ml/min demonstrated that hyperkalemia in the ranges of 5.0-6.0 meq/L (using an average of six measurements per patient) appeared to be well tolerated. 47 Adaptive increases in circulating catecholamines, aldosterone, and augmentation of renal and gastrointestinal (GI) potassium elimination are thought to blunt hyperkalemia development in CKD and could partially explain this apparent disconnect in mortality relative to non-CKD patients.…”
Section: Hyperkalemia With Ckdsupporting
confidence: 77%
“….0, 5.0-5.5, 5.5-6.0, 6.0-6.5, and .6.5 meq/L, respectively). 38 Another retrospective trial analyzing 90-day mortality in 2596 Danish patients with heart failure post-AMI also supports that a serum potassium .5.1 meq/L is associated with higher risk of death (HR, 2.3; 95% CI, 1.4 to 3.6). 39 The studies by Goyal et al 37 and Grodzinsky et al 38 are strengthened by use of robust adjustment models that control for baseline risk, medications, PCI use, and other pertinent factors.…”
Section: Hyperkalemia During Acute Myocardial Infarctionmentioning
confidence: 88%
See 1 more Smart Citation
“…With the ethical conflict of not treating a potentially fatal pathology, no randomized interventional hyperkalemia treatment trials have been published. Observational data suggest that lowering potassium levels in patients with hyperkalemia is associated with lower mortality (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Our results were found to be in correlation with the results obtained by previous authors who have reported a male preponderance in AMI groups of their respective studies. 14,15 Hypokalemia was found in 24% cases, hyperkalemia in 6% and 70% were normokalemic. Our results were in correlation with the results obtained by studies of past literature, which have reported that prevalence of hypokalemia in AMI patients varies from 9 % to 25 %.…”
Section: Discussionmentioning
confidence: 99%